Effect of post-pctivation potentiation enhancement induced using elastic resistance bands on female track and field jumpers - Chaware, U.; Lum, D. (SportMont, 2024)
Elastic Resistance Bands (ERB) are widely used by athletes separately and in conjunction with heavy loads to activate muscles and improve various athletic abilities. The study aimed to assess the effect of ERB training while warm-up among female track and field jumpers. In the randomized between-group parallel design, 14 athletes were separated into ERB (age: 21±2.16 years, height: 165.6±8.24 cm, body mass: 57.97±4.28 kg) and control (CON) (age: 21.42±2.29 years, height: 164.57±8.54 cm, body mass: 56.57±5.18 kg) groups. A baseline test for CMJ was performed after a general warm-up. Upon completion, both groups performed similar specific pre-competition warm-up drills, with the ERB group performing the exercises using an elastic resistance band. Both groups were tested for follow-up measurements. Significant time x group interaction was observed for jump height (p=0.024, ?p2=0.36) and take-off force (p=0.039, ?p2=0.30). Significant differences in baseline and follow-up measurements were found in ERB groups for all the dependent variables except peak speed (jump height p=0.006, g=0.48; take-off force p=0.009, g=0.99; take-off speed p=0.046, g=0.55, and max. concentric force p=0.005, g=0.87). The results suggest that performing running drills with ERB may have the potential to enhance lower limb force generation capacity, as indicated by improvements in CMJ height and take-off force in this study. While these findings are promising, they should be interpreted with caution due to the small subsample size. ERB could be considered as a potential component of warm-up routines for track and field athletes, particularly in situations of low logistical availability. However, further research involving larger sample sizes is necessary to confirm these preliminary findings regarding the efficacy of ERB in warm-up protocol.